Examining the Negative Impact of Sexual Harassment in Valenzuela City at Selected Factory in Paso de Blas: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In the workplace, sexual harassment undermines gender equality, leads to discriminatoryhiring practices, and negatively influences employees' dignity and well-being. Sexualharassment is a kind of sex discrimination. If ignored, it can result in substantial expenses forbusinesses due to productivity loss, low worker morale, absenteeism, and employee turnover.It causes psychological anguish and stress for victiMs. With a few notable exceptions,investigations into workplace sexual harassment have been conducted primarily in developednations. Even in affluent nations where workplace sexual harassment has been thoroughlyexamined, empirical research has not produced conclusive results about its causes andeffects, both personally and organizationally. Studies have shown that even small acts ofsexual harassment, such as making obscene remarks or making the hottest jokes, over timecan result in severe psychological discomfort. The perceived aspect of workplace sexualharassment is a significant issue. There may be differences between what sexual harassmentis to men and women. Given that men regarded fewer activities as sexual harassment in hisstudy. According to Champlin K. Oldham (2019), sexual harassment refers to unwelcomesexual advances, comments of a sexual nature, requests for sexual favors, and harassmentor comments about an individual’s gender, all of which create a hostile work environment.Most commonly, sexual harassment is perpetrated by someone in a position of authority overthe victim, such as an employer, supervisor, or teacher. Sexual harassment attacks no sexualorientation. It can be experienced by both males and females in any form in any workingenvironment; sexual harassment is not only a physical crime against women and men but hasbeen found responsible for their poor physical and emotional health. Have reported thatsexual harassment can have negative academic, psychological, and behavioral impacts onthe victim. Sexual harassment affects the mental health of both genders. Sexual harassmentcan cause low self-esteem, post-traumatic syndrome (PTSD), anxiety, depression, and sexualdysfunction. Sexual harassment happens in the working environment. The employer commitssexual violence to their employee in exchange for a promotion or any other position in acompany. Women and men experience sexual harassment in their working environment.Women are discriminating against their gender, and it will cause them to quit their jobs toavoid any form of sexual harassment. Men have experienced this sexual harassment in theirworking environment by their male bosses. They will touch and caress their thighs or their armor whisper to their ears some sexual statement. This research determines the negative impactof sexual harassment on every individual in our society.The researchers answered the question: what is the assistance made by the company or localauthorities to the employees who are victims of sexual harassment in Valenzuela city? Rankone, “.Advice or options available before filing the complaint.” With a mean score of 2.50, it isinterpreted as partially Agreeable. Rank two, “.Referral to an agency offering professionalhelp,” with the same mean score of 2.50, interpreted as partially Agreeable. Rank three,”Giving counseling to the victim of the harassment,” with the same mean score of 2.50,interpreted as Partially Agree. Rank four, “Action is taken to address the concerns raised,potential including training and discipline.” with a total mean score of 2.50 interpreted PartiallyAgree.
Keywords: Criminology